DESA DAN HAK-HAK TRADISIONAL - Suparman, Asep (Jurnal Wawasan Yuridika, 2012)
Village, as a social identity has already become a social institution which has an important position. Village with different kinds of its typology has been a basis of society lives, and has autonomy in the framework of regulating authority order and management order of people, local institution, and economic resource. Traditional rights possessed by villages are acknowledged by the state. This is reflected in provision of article 18 B of 1945 Constitution, and provision of article 1 number 1 of Act No. 6 year 2014. By acknowledgment of the state, traditional rights will never vanish although there is a paradigm shift. More over, there is a proverb âberat sama dipikul, ringan sama dijinjingâ.Keywords: autonomy, traditional rights.